Prediksi Umur Lelah Pegas Ulir Suspensi Depan Minibus yang dikemudikan di Atas Permukaan Jalan Datar, Menanjak dan Menurun Berazaskan Pendekatan Strain-Life - Azhari; Zainal (Journal of Engineering and Science, 2022)
This study aims to evaluate the effect of road conditions on the fatigue life of coil springs using the strain life approach. This approach is accomplished by measuring the strain signal in the coil spring at the front of the car with a strain gauge at the component's critical point. Three different types of roads, namely flat roads, uphill roads, and downhill roads were chosen to test the strain signals obtained. After analysis, it was found that the fatigue life of the coil spring on the downhill road had the lowest value of 1.52e+4 cycles before it broke. This value is 54% lower than the fatigue life on flat roads and 96% lower than on uphill roads. This result is due to the braking factor on the way down which puts a higher tension on the coil springs, reducing their fatigue life. This study can contribute to the automotive industry to consider different road conditions in the design and testing of their products, especially in critical components such as coil springs. The strain life approach has also been shown to be effective in evaluating the fatigue life of automobile components, which can help improve vehicle quality and safety.